Accommodation means used by women traveling alone - Oliveira, Rodrigo Ribeiro de; Ghirotti, Gabryela Martins; Oliveira, Wenya e Silva (Brazilian Journal of Production Engineering, 2021)
The present study aims to identify the means of accommodation used by Brazilian women traveling alone and the determining criteria for this choice, in addition to understanding the difficulties faced, from their perspectives. In this way, the work still addresses the role of women as a tourist who travels alone and its obstacles. In June 2021, a focus group study was carried out, in a virtual way, with the participation of five women. The speeches were recorded, transcribed and categorized, based on the discussion focused on “Brazilians traveling alone and the means of accommodation”, a theme that allowed the participants to report their own experiences and contribute to obtaining results in the research. It was evident how important solo travel is as a way of expressing freedom and opposition to the models established in society and that the criteria for choosing accommodation facilities are not restricted to the fact of being a woman traveling alone.